Preparos dentais para coroas totais anteriores cerâmicas - Faria, Ivan Ribeiro de [UNESP]; Segalla, José Cláudio Martins [UNESP]; Silva, Regina Helena Barbosa Tavares da [UNESP]; Pinelli, Lígia Antunes Pereira [UNESP]; Reis, José Maurício dos Santos Nunes [UNESP] (My University, 2011)
The aim of this study is to describe, illustrate and discuss a simple, effective and rational method for preparing anterior all-ceramic restorations. This procedure uses a reduced number of diamond burs and a few clinical steps. The biological, mechanical, functional and aesthetic principles are obtained in a reasonable manner, regarding the requirements’ supported by the contemporary aesthetic dentistry. At the end of reading, it is expected that the professionals understand the design of the axial and cervical dental walls. Finally, the dental preparations will be made in a rapid and efficient manner. Despite the citation of specific diamond burs, it is expected that the reader use them as a reference. The understanding of their geometric configuration and volume are more important than their manufacturer’s reference number. Other manufacturers have diamond burs with the same geometric configuration of those recommended in this technique. Thus, the clinical professional must select the diamond points according to their manufacturer of choice.

O objetivo deste trabalho é descrever, ilustrar clinicamente e discutir uma forma efetiva, simples e racional de preparos dentais para coroas totais anteriores cerâmicas. Essa técnica visa à confecção de preparos dentais por meio da utilização de número reduzido de etapas clínicas e pontas diamantadas. Os princípios biológicos, mecânicos, funcionais e estéticos são atingidos de maneira lógica, dentro dos requisitos regidos pela odontologia estética contemporânea. Ao final da leitura, espera-se que o cirurgião dentista compreenda a configuração das paredes axial e cervical dos preparos para coroas totais anteriores cerâmicas e realize o procedimento de maneira rápida e eficiente. Apesar da citação numérica específica das pontas diamantadas utilizadas, espera-se que o leitor as utilize como referência, lembrando ser mais importante a compreensão de sua configuração geométrica e volume. Outros fabricantes possuem pontas diamantadas com a mesma configuração geométrica das pontas recomendadas nesta técnica. Dessa forma, cabe ao profissional selecionar as pontas diamantadas de acordo com seu fabricante de eleição.
Dental preparations for anterior all-ceramic crown restorations
Keywords: Fixed partial denture; Dental preparations; Ceramic; Prótese parcial fixa; Preparo do dente; Cerâmica